Pelatihan Dan Pemanfaatan E-Commerce Sebagai Media Pemasaran Produk Umkm Di Desa Donowati - Waode Intan Chomariah; Ririt Iriani Setiawati; Putra Perdana (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2022)
Mechanical advancements lead society towards effectiveness in exchanging exchange exercises. In its elemental, innovation assumes a part and turns into an option for society to go through with exchanges. This innovation is adjusted rapidly believing capacity to be a mechanism for exchanges should be possible anyplace and whenever. In accordance with mechanical turns of events, online business has turned into an additional coordinated method for exchanges among purchasers and venders. The common sense and variety of installment systems are the qualities of online business so that an ever increasing number of individuals are utilizing the stage. Be that as it may, there are additionally numerous MSME entertainers who don't grasp the ongoing improvement of exchange innovation, particularly the MSME entertainers in Donowati town. Most MSME entertainers in Donowati town don't figure out the activity of online business. The presence of this local area administration movement plans to clarify how the method involved with presenting the local area for internet business and its varieties. The technique completed during administration exercises utilizes distinct subjective exploration strategies through socialization and appraisal of the improvement of the utilization of web based business to SME entertainers in Donowati town.